Impact of kinetic facade design to enhance daylight performance for office building in Cyberjaya Malaysia - Moesas, Omran Subhi (2021)
Some critical directions of building facade are highly exposed to the sun and it requires a smarter shading device than conventional shading devices that fail to adapt with nature of sun motion may occur during day, month and seasons. In this study, parametric scripts were written to propose six Kinetic facades design to enhance daylight performance followed by theoretical comparison. The case study was selected to be on Stare Central office building in Cyberjaya, Malaysia to be as virtual model which was built in Rhino for the daylight simulation and to conduct physical daylight measurement by Lux meter device to validate the simulation through a comparison between the physical daylighting measurement with the virtual simulation. Parametric Daylight simulation was performed on Rotating Facade design through Rhino software using plugins Grasshopper and Diva with a Radiance interface based on LEED V4.1 criteria. The daylight simulation was divided into four phases, starting with annual simulation for benchmark (the actual existing facade) and different glaze materials followed by simulations for facade parameters (size & rotation angle) ending with the hourly daylight simulation. The annual simulation was conducted using Daylight Dynamic Performance Metrics specifically; Spatial-Daylight-Autonomy (sDA300/50%) and Annual- Sunlight-Exposure (ASE1000/250hr). While the Hourly simulation depend on modified metric which is Hourly Spatial daylight Autonomy HsDA and Hourly sun exposure HSE from 8AM to 6PM in four days that represent the equinox and solstice days. From the results obtained, benchmark cases illustrate the need of highperformance facade to decrease the recorded dangerous values caused by direct sun radiation. none of the glaze materials achieved credit of LEED standards except Generic Translucent panel 20% with 1 credit. The rotation angle 20˚ and 30˚ of rotating façade have achieved three credits of LEED in east and west respectively as a static system. Finally, the study proposed two optimized dynamic systems able to adapt hourly according to the sun position and achieve higher performance than optimum static configure based on comparison.